Mesh repairing using topology graphs - Charton, Jerome; Baek, Stephen; Kim, Youngjun (한국CDE학회, 2021)
Geometrical and topological inconsistencies, such as self-intersections and non-manifold elements, are common in triangular meshes, causing various problems across all stages of geometry processing. In this paper, we propose a method to resolve these inconsistencies using a graph-based approach. We first convert geometrical inconsistencies into topological inconsistencies and construct a topology graph. We then define local pairing operations on the topology graph, which is guaranteed not to introduce new inconsistencies. The final output of our method is an oriented manifold with all geometrical and topological inconsistencies fixed. Validated against a large data set, our method overcomes chronic problems in the relevant literature. First, our method preserves the original geometry and it does not introduce a negative volume or false new data, as we do not impose any heuristic assumption (e.g. watertight mesh). Moreover, our method does not introduce new geometric inconsistencies, guaranteeing inconsistency-free outcome.